In Congress, August 26, 1776. Whereas, in the course of the present war, some commissioned and non-commissioned officers of the Army and Navy, as also private soldiers, marines and seamen, may lose a limb, or be otherwise so disabled . ([publisher not identified], 1778)
Resolution of the Continental Congress granting disability payments; followed by a second resolution of Sept. 25, 1778 extending payments to those disabled in the course of the war before Aug. 26, 1776.